Control of lymph node activity by direct local innervation. Issue 9 (September 2022) - De Virgiliis, Francesco; Oliva, Valeria Maria; Kizil, Burak; Scheiermann, Christoph
Abstract : The nervous system detects environmental and internal stimuli and relays this information to immune cells via neurotransmitters and neuropeptides. This is essential to respond appropriately to immunogenic threats and to support system homeostasis. Lymph nodes (LNs) act as sentinels where adaptive immune responses are generated. They are richly innervated by peripheral sympathetic and sensory nerves, which are responsible for the local secretion of neurotransmitters by sympathetic fibers, such as norepinephrine, and neuropeptides by sensory fibers, including calcitonin gene-related peptide (CGRP) and substance P. Additionally, time-of-day-dependent oscillations in nerve activity are associated with differential immune responses, suggesting a potential role for neuroimmune interactions in coordinating immunity in a circadian fashion. Here, we discuss how LN activity is controlled by local innervation. Highlights: Neuroimmune interactions play a critical role in supporting system homeostasis and modulating immune responses to potentially dangerous stimuli. Lymph nodes (LNs) are key hubs of the immune system; they are richly innervated by sympathetic and sensory fibers. Sympathetic fibers innervate the peripheral as well as the deep cortical and paracortical regions of the LNs, while sensory fibers mostly innervate the capsule and outer medullar regions. Neurotransmitters, such as norepinephrine, and neuropeptides, including calcitonin gene-related peptide (CGRP) and substance P are released by sympathetic and sensory fibers, respectively and can locally control LN physiology. Diurnal oscillations of environmental stimuli are associated with changes in nerve activity, which affects LN function in a time-of-day-dependent manner.